Local Wisdom-Based on Development of the Environment and Atmosphere Aspect of Berastagi Night Tourism - Selly Veronica; Nurlisa Ginting; Amy Marisa (International Journal of Architecture and Urbanism, 2020)
Nowadays, tourism has an important place in urban development, where every city competes to improve their tourism. Night tourism, as the new strategy in tourism development, needs to be given attention from the stakeholder. The two most important aspects of the night tourism development are environmental and night atmosphere. Increasing the aspect of night tourism cannot be separated from the local wisdom-based. Berastagi is the most popular tourist destination in Karo Regency, which has a night tourism destination. Not only it, but Berastagi also has an authentic culture from the Karonessse tradition. Unfortunately, both of these potentials have not developed yet as the strength of tourist attraction in Berastagi. This paper aims to find how are the development of the environment and atmosphere aspect of Berastagi Night Tourism based on local wisdom. This research used a descriptive qualitative method which analyzes data collected by field observation and depth interview. The study shows that involving local wisdom in developing the environment and night atmosphere can build a specific identity for the town night tourism.